Asymmetric Total Synthesis and Determination of the Absolute Configuration of (+)-Srilankenyne via Sequence-Sensitive Halogenations Guided by Conformational Analysis - Jang, Hongjun; Kwak, Soo Yeon; Lee, Dongjoo; Alegre-Requena, Juan V.; Kim, Hyoungsu; Paton, Robert S.; Kim, Deukjoon (Organic Letters, 2021)
This first asymmetric total synthesis of (+)-srilankenyne (1), a halogenated C15 tetrahydropyran acetogenin isolated from Aplysia oculifera, features a sequence-sensitive process guided by conformational analysis to solve the challenging problem of introducing halogens. A competing semipinacol rearrangement during the installation of C(12)-bromide was suppressed by our A1,3 strain-controlled bromination protocol with support from X-ray crystallographic and computational studies. The C(10)-chloride was then placed by the Nakata chloromesylate-mediated chlorination.